1996
DOI: 10.1126/science.271.5251.963
|View full text |Cite
|
Sign up to set email alerts
|

From Topographies to Dynamics on Multidimensional Potential Energy Surfaces of Atomic Clusters

Abstract: Multidimensional potential energy surfaces for systems larger than about 15 atoms are so complex that interpreting their topographies and the consequent dynamics requires statistical analyses of their minima and saddles. Sequences of minimum-saddle-minimum points provide a characterization of such surfaces. Two examples, Ar 19 and (KCI) 32 , illustrate how topographies govern tendencies to form glasses or “focused” structures, for example, crystals or folded prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
172
0
4

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(176 citation statements)
references
References 36 publications
(13 reference statements)
0
172
0
4
Order By: Relevance
“…with F ) 4, there are many transitions from all bands to the GM band (6). The peak in the frequency of transitions to the GM occurs at band 3.…”
Section: Band Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…with F ) 4, there are many transitions from all bands to the GM band (6). The peak in the frequency of transitions to the GM occurs at band 3.…”
Section: Band Transitionsmentioning
confidence: 99%
“…This is in contrast to some larger Lennard-Jones and Morse clusters, which are good examples of glass-formers. 6 The F parameter of the Morse potential varies the potential's range: the smaller the value of F, the longer the range of the potential. Morse potentials fit to known diatomic molecule spectra have values of F between 3 and 7.…”
Section: Introductionmentioning
confidence: 99%
“…This characterization of the PES helps to explain the initial presence of the metastable isomers in the experiments by Jarrold and coworkers. [14,15] The energy landscape efficiently 'funnels' high energy structures into rocksalt-type minima [52,53]. However, the barriers between the different funnels are large, leading to a separation of time scales for relaxation down the PES to a rocksalt structure and conversion of the metastable nanocrystals to the global minimum.…”
Section: Global Optimizationmentioning
confidence: 99%
“…For years, potential energy surfaces have been widely studied and regarded as an important tool to understand kinetics and dynamics of various systems from the relaxation of atomic clusters [1][2][3] to the problems of protein folding. 4 Recently, master equation dynamics, 5 as a method complementary to molecular dynamics (MD), has also been applied to the study of kinetics on a PES.…”
Section: Introductionmentioning
confidence: 99%
“…Ball and Berry 11 first addressed this problem by using a ''sequence sampling'' method to obtain samples of some preknown full PESs of Ar 11 and Ar 13 . The authors have shown that with ''sequence sampling'', the constructed sample PES can be used to predict the slowest relaxation mode with convergence to within better than a factor of two with about 100 monotonic sequences 2,3 where each sequence is a ''minimum-saddle-minimum-...-minimum'' series with monotonically increasing energy values for the minima. This corresponds to about 40% and 20% of the sampling ratio (defined as the ratio between the numbers of energy minima in the sample PES and in the full PES) for the full PESs of Ar 11 and Ar 13 , respectively.…”
Section: Introductionmentioning
confidence: 99%